Esensialisme Pengembangan Sistem Pembelajaran Pendidikan Kewarganegaraan Siswa dalam Toleransi Keberagaman Budaya - Manullang, Ester Reviani; Yunita, Sri (PAKAR Pendidikan, 2023)
Indonesian culture is a unique and diverse culture that is sometimes referred to as multicultural. In connection with the diversity of the Indonesian nation, conditions with attitudes that do not reflect a sense of pride in culture tend to become conflicts of quarrels or disagreements between conflicting parties. This study aims to determine the importance of essentialism in the development of a civic education learning system that integrates tolerance values towards cultural diversity. The method used in this research uses qualitative research methodology with a literature study approach. The analysis method used in this research is descriptive analysis. Based on the results of the research that has been done, it is found that there are a number of cases of freedom of religion/belief (KBB) that indicate losses, inconveniences, and disturbances in the aspect of freedom of religion/belief (KBB). Through the analysis conducted, it can be concluded that the civic education learning system must be improved and developed in order to outstand the value of tolerance towards students who are the younger generation who continue the development of the Indonesian Nation, which ensures that especially educators must have the value of tolerance regulated by the state and students must be able to follow the understanding of good and correct civic values